Latin America: The Pitfalls of U.S.-Mirrored Presidential System in Banana Republics - Marsili, M. (Boletín de la Academia de Yuste, 2023)
There is something in common between the countries located in the Western Hemisphere—and is not just the geographic position. Latin America boasts an impressive string of coups, compared to the stable democracy of its American neighbor. Recent events in Brazil after Lula was sworn in for a third term as president against incumbent Bolsonaro, reminded us of the assault on the U.S. Capitol on January 6, 2021, that disrupted a joint session of the Congress in the process of affirming the presidential election results which kicked Donald Trump out of the White House. The election protests in Brazil began shortly after the conclusion of the general election’s second round on October 30, 2022, in which Luiz Inácio Lula da Silva was elected president, and picked on January 8, 2023, when thousands of far-right supporters of former President Jair Bolsonaro stormed all three branches of Brazil’s government in the capital calling for military intervention. There are similarities and differences between the Brazil attack compared to January 6 attack in the United States. Both Bolsonaro and Trump have contested their electoral defeats, amplifying unsupported conspiracy theories of voter fraud. Also, the Venezuelan presidential crisis which lasted from 2019 to 2023 was paved by fraudulent elections.